Enhancing Reproductive Performance of Freshwater Finfish Species through Dietary Lipids - Donald Torsabo; Sairatul Dahlianis Ishak; Noordiyana Mat Noordin; Ivan Chong Chu Koh; Muhammad Yazed Abduh; Benedict Terkula Iber; Meng-Kiat Kuah; Ambok Bolong Abol-Munafi (Aquaculture Nutrition)
Dietary lipid manipulation in the feed of commercially cultured finfish is used not only to improve production and culture but also to enhance their reproductive performances. The inclusion of lipid in broodstock diet positively affects growth, immunological responses, gonadogenesis, and larval survival. In this review, existing literature on the importance of freshwater finfish species to aquaculture and the inclusion of dietary lipid compounds in freshwater fish feed to accelerate the reproduction rate is being summarized and discussed. Although lipid compounds have been confirmed to improve reproductive performance, only a few members of the most economically important species have reaped benefits from quantitative and qualitative lipid studies. There is a knowledge gap on the effective inclusion and utilization of dietary lipids on gonad maturation, fecundity, fertilization, egg morphology, hatching rate, and consequently, larval quality contributing to the survival and good performance of freshwater fish culture. This review provides a baseline for potential future research for optimizing dietary lipid inclusion in freshwater broodstock diets.